Exploring challenges to teamwork and strategies to enhance teamwork in the emergency department of a private hospital in Gauteng - Filmalter, Cecilia Jacoba (University of Pretoria, 2022)
Thesis (MSc (Nursing Science))--University of Pretoria, 2022.